Intervensi Kebijakan Politik Hukum dalam Penyelenggaraan Ketahanan Pangan - Nugraha, Harry Setya; Utomo, Setiyo (Legal Spirit, 2024)
Implementing food security within the provisions of applicable laws and regulations to accelerate the realization of community welfare through improving services, empowerment, and community participation, as well as increasing regional competitiveness by taking into account the principles of democracy, equality, justice, and the uniqueness of a region. One of them is the Berau Regency, which still needs a statutory policy that regulates food security. Even if there is a policy that regulates food security, this policy is not statutory. It can be considered insufficientinsufficient to resolve the problem of food security in the Berau Regency. This research aims to analyze and provide recommendations for regional regulations regarding food security. The method used is mixed research methods. The research results show that East Kalimantan has the highest level of food security. However, there are still quite a lot of problems faced by the region in implementing food security, namely the conversion of agricultural land, resulting in environmental damage and global climate change. Legal and political policy intervention is a form of fulfilling the obligations and commitment of regional governments as regional government administrators in the context of implementing food security and fulfilling needs to resolve various food security problems that are currently occurring, as well as an effort to prevent other food security problems in the future.